THE REFUTATION OF AL-GHAZĀLĪ AND THE DEFENCE OF IBN RUSHD AGAINST THE THREE METAPHYSICAL PROBLEMS OF THE PHILOSOPHERS - Surajiyo, Surajiyo; Astanto, Sugeng (Sekolah Tinggi Agama Islam Sadra, 2025)
Amid the many complex and radical philosophical debates, one of the most fascinating and widely discussed issues among scholars and philosophy enthusiasts is the intellectual confrontation between al-Ghazālī and Ibn Rushd. The most prominent philosophical dispute between the two revolves around three major metaphysical problems: the eternity of the world, God’s knowledge of particular events, and the denial of bodily resurrection. Both thinkers offer different interpretations of Qur’anic texts through a philosophical lens. Interestingly, although both belong to the same Islamic intellectual tradition, their opposing arguments have generated deep and enduring controversy. This study employs a descriptive research method, specifically a library-based approach, focusing on literature that discusses the philosophical thoughts of al-Ghazālī and Ibn Rushd. Within this method, processes of classification, data analysis, and conclusion drawing are carried out. Accordingly, the research also utilizes comparative, analytical, and synthetic methods to obtain a comprehensive understanding of their metaphysical perspectives. As a result, the debate between the two continues to be passed down and colors the study of Islamic philosophy, including having consequences in the context of philosophical themes.